Spectrum of developmental anomalies of the central nervous system encountered in a tertiary care hospital - Panda, Subhasish; Dash, Subhashree; Bhagat, Savitri; Panda, Braja Bihari (International Journal of Research in Medical Sciences, 2018)
Background: Congenital Central Nervous System (CNS) anomalies have typical and characteristic imaging features. Imaging plays a pivotal role in their diagnosis. This study aims to determine the prevalence and spectrum of the various congenital anomalies of the CNS diagnosed at our institution, and to classify the imaging features according to an approved classification system. Methods: This cross-sectional study was conducted on infants and children below 12 years of age attending the Department of Radiodiagnosis of our Institution, for radiographic investigation of congenital anomalies in CNS through Computerised Tomography and/or Magnetic Resonance Imaging, over a period of one year. The spectrum of imaging features was analysed as per approved classification and corroboration with their clinical background. The prevalence of each type of congenital anomaly was also assessed. Results: A total number of 43 developmental anomalies of the central nervous system were encountered in 33 patients over a period of one year. The most common anomalies encountered were partial corpus callosal agenesis, heterotopic grey matter and Dandy Walker malformation. The total prevalence of CNS anomalies was 4.22%. The most common clinical symptoms in these patients were seizures followed by focal neurological deficit. The imaging findings of each anomaly are discussed. Conclusions: Developmental anomalies of CNS are encountered in 4.22% of patients in our Institution, with partial corpus callosum agenesis being the most frequent entity. Familiarity with imaging findings of these malformations is mandatory for every radiologist.